Correction of a genetic disease in mouse via use of CRISPR-Cas9 - Wu, Yuxuan; Liang, Dan; Wang, Yinghua; Bai, Meizhu; Tang, Wei; Bao, Shiming; Yan, Zhiqiang; Li, Dangsheng; Li, Jinsong (Cell stem cell, 2013)
The CRISPR-Cas9 system has been employed to generate mutant alleles in a range of different organisms. However, so far there have not been reports of use of this system for efficient correction of a genetic disease. Here we show that mice with a dominant mutation in Crygc gene that causes cataracts could be rescued by coinjection into zygotes of Cas9 mRNA and a single-guide RNA (sgRNA) targeting the mutant allele. Correction occurred via homology-directed repair (HDR) based on an exogenously supplied oligonucleotide or the endogenous WT allele, with only rare evidence of off-target modifications. The resulting mice were fertile and able to transmit the corrected allele to their progeny. Thus, our study provides proof of principle for use of the CRISPR-Cas9 system to correct genetic disease.